Effect of Avocado Seed Flour Nugget on Organoleptic Tests - Eliska, Eliska; Dur, Sajaratud (Poltekita : Jurnal Ilmu Kesehatan, 2024)
Avocado seeds contain a lot of starch and can be processed into foods such as avocado seed flour (TBA). TBA is classified as low-protein flour but has a lot of nutritional content, so it can be made into noodles or other food products. This research aimed to determine the acceptability of avocado seed flour nuggets with chicken, catfish, and shrimp variants. The research design in this study is a pure experiment with a simple experimental design. A simple experimental design is also called a posttest-only control group design. This research design was a nugget design with 25% avocado seed flour and 25% tapioca flour with three treatments (three flavor variants), chicken, catfish, and shrimp (50%). The results of this study showed that there were significant differences in the chicken, catfish, and shrimp nugget variants based on color categories because the results were p<0.05. In terms of texture, the test shows a p-value of >0.05, which means that there is no real difference between the three variants of avocado seed nuggets. In conclusion, this research is based on the results of the ANOVA test on avocado seed nuggets with chicken, catfish, and shrimp variants. The results obtained were that there were real differences in the chicken, catfish, and shrimp nugget variants based on the color, taste, and aroma categories. Meanwhile, in the texture category, the test results obtained were that there were no real differences between the three avocado seed nugget variants.